2022
DOI: 10.1186/s12711-022-00737-3
|View full text |Cite
|
Sign up to set email alerts
|

Impact of linkage disequilibrium heterogeneity along the genome on genomic prediction and heritability estimation

Abstract: Background Compared to medium-density single nucleotide polymorphism (SNP) data, high-density SNP data contain abundant genetic variants and provide more information for the genetic evaluation of livestock, but it has been shown that they do not confer any advantage for genomic prediction and heritability estimation. One possible reason is the uneven distribution of the linkage disequilibrium (LD) along the genome, i.e., LD heterogeneity among regions. The aim of this study was to effectively u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…SNP-based heritability ( h 2 ) estimates were relatively higher for stem height at the first branch ( h 2 = 0.35), followed by branching ( h 2 = 0.25), and branching levels ( h 2 = 0.19). These estimates could be attributed to LD unevenness or heterogeneity among marker regions due to overestimation or underestimation, as postulated by [ 76 ].…”
Section: Discussionmentioning
confidence: 96%
“…SNP-based heritability ( h 2 ) estimates were relatively higher for stem height at the first branch ( h 2 = 0.35), followed by branching ( h 2 = 0.25), and branching levels ( h 2 = 0.19). These estimates could be attributed to LD unevenness or heterogeneity among marker regions due to overestimation or underestimation, as postulated by [ 76 ].…”
Section: Discussionmentioning
confidence: 96%
“…Block size can affect prediction accuracy of single-trait or multi-trait Bayesian models fitting heterogeneous genetic (co)variances [41,45]. In the present study, the prediction accuracy of mbBayesAB for different block sizes (one SNP; a group of 25, 50, 100, 200 adjacent SNPs or the whole genome) was compared.…”
Section: Number Of Snps In Genome Block Partitioningmentioning
confidence: 99%
“…Therefore, the higher marker density, the more accuracy of GS and better selection effect. In addition, some studies have shown that grouping SNPs based on regional LD can effectively reduce the adverse effect of the uneven distribution of LD on the genome, and greatly improve the efficiency of high-density SNP data for genome prediction and heritability estimation (Ren et al, 2022).…”
Section: Influential Factors Of the Gs Accuracymentioning
confidence: 99%